Representational Transition Patterns of Pre-service Teachers in Solving Convergent Sequence Problems - Nursupiamin; Rochaminah, Sutji; Sudarsana, I Wayan (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study investigates the representational transition patterns of pre-service teachers in solving convergent-sequence problems, with a focus on how they utilize symbolic, visual, and verbal representations. Using a qualitative phenomenological design, seven pre-service mathematics teachers were purposively selected based on their dominant representation modes (symbolic, visual, verbal). Participants solved a convergent-sequence task, and their problem-solving processes were analyzed using a modified Colaizzi method, with triangulation ensuring the validity of the findings. Three key patterns emerged: a stagnant reliance on a single representation mode (symbolic or verbal), a linear transition from visual to symbolic forms, and a complementary use of symbolic and verbal representations. No cyclic or complex transition patterns were identified, indicating limited representational fluency. The findings highlight the dominance of symbolic representations among pre-service teachers, with some exhibiting limited representational flexibility. The study suggests that fostering representational fluency, where students can effectively transition between different forms, is crucial for deeper conceptual understanding, especially in abstract topics like convergent sequences. Pedagogically, the study underscores the importance of instructional strategies that encourage the integration and transition across symbolic, visual, and verbal representations. This research contributes to the understanding of representational transition patterns in real analysis, an area often underexplored in mathematics education, and offers insights for improving teacher preparation programs.